Solid freeform fabrication. - Crawford, R.H.
Researchers at Austin have been working on technologies termed solid freeform fabrication (SFF) or, as reported in the popular press, desktop manufacturing, rapid prototyping, and layered manufacturing. Such processes have the potential to produce accurate, structurally sound 3-D renditions of objects designed with computers and manufactured directly from a CAD database, without part-specific tooling or human intervention, and to make them available to the user in minutes or hours. The benefits include greatly reduced prototyping cost and design time and reliability to achieve, in one operation, shapes that would otherwise require multiple operations or in some cases be impossible to produce with standard techniques. Automated manufacturing technologies in general are well suited to large production numbers, but ill suited to low-volume runs. In the latter case, the components are too few to adequately amortize the cost of part-specific tooling; instead, they are typically made by hand at much greater unit cost and longer completion times. Nor is it a completely desirable low-volume option to interface CAD systems with numerically controlled (NC) machining centers-in essence, computer controlled material removal systems-because so much human intervention is involved in producing NC programs and setting up and supervising NC systems. In fact, the low-volume production arena is exactly where SFF slashes cost and time to completion
Keywords: CAD database; Desktop manufacturing; Layered manufacturing; Rapid prototyping; Reduced design time; Reduced prototyping cost; Solid freeform fabrication